Runners do not push off the ground but fall forwards via a gravitational torque - Romanov, N.; Fletcher, G. (Sports Biomechanics, 2007)
The relationship between the affect and timing of the four forces involved in running (gravity, ground reaction force, muscle force, and potential strain energy) is presented. These forces only increase horizontal acceleration of the centre of mass during stance but not flight. The current hierarchical models of running are critiqued because they do not show gravity, a constant force, in affect during stance. A new gravitational model of running is developed, which shows gravity as the motive force. Gravity is shown to cause a torque as the runner's centre of mass moves forward of the support foot. Ground reaction force is not a motive force but operates according to Newton's third law; therefore, the ground can only propel a runner forward in combination with muscle activity. However, leg and hip extensor muscles have consistently proven to be silent during leg extension (mid-terminal stance). Instead, high muscle-tendon forces at terminal stance suggest elastic recoil regains most of the centre of mass's height. Therefore, the only external motive force from mid-terminal stance is gravity via a gravitational torque, which causes a horizontal displacement. The aim of this paper is to establish a definitive biomechanical technique (Pose® method) that is easily taught to runners (Romanov, 2002): falling forwards via a gravitational torque while pulling the support foot rapidly from the ground using the hamstring muscles.